IC 9374 The Prevalence Of Overexertion Injuries In The U.S. Metal-Nonmetal Mining Industry - Debra A. Griffith (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The U.S. Bureau of Mines currently is researching the relationship between the level of back strength and the probability of low-back injury. This report is a review of the literature and statistics on over-exertion injuries. Overexertion continues to be a significant source of injury in metal and nonmetal mining, accounting for approximately 24 pct of all injuries yearly. These injuries, particularly to the lower back, can be very expensive in human and monetary terms. An examination of the accident data on overexertion injuries is necessary to provide a background for research into prevention and/or amelioration of those in-juries. The job categories outlined in the Accident Data Analysis data base most affected are "Mechanic/Electrician" and "Mill/Plant Worker." The age group most affected is "30-39" years, and the experience group most affected is "0-.99" years. The most prevalent type of overexertion injury is "Strain/Sprain," and the trunk is the body part most often involved in an overexertion injury.